Innate cell communication kick-starts pathogen-specific immunity - Rivera, Amariliz (Nat Immunol, 2016)
Innate cells are responsible for the rapid recognition of infection and mediate essential mechanisms of pathogen elimination, and also facilitate adaptive immune responses. We review here the numerous intricate interactions among innate cells that initiate protective immunity. The efficient eradication of pathogens depends on the coordinated actions of multiple cells, including innate cells and epithelial cells. Rather than acting as isolated effector cells, innate cells are in constant communication with other responding cells of the immune system, locally and distally. These interactions are critically important for the efficient control of primary infections as well for the development of ‘trained’ innate cells that facilitate the rapid elimination of homologous or heterologous infections.